Time and Cost Control Analysis of the Construction of the Joyoboyo Zoo Intermodal Terminal Pedestrian Tunnel Using the Critical Path Method - Sartiyana, I Ktut Riagung; Nugroho, Laksono Djoko; Muhammadun, Haris (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
This study aims to analyse the effectiveness of Critical Path Method (CPM) in controlling the time and cost of the Pedestrian Tunnel construction project connecting Joyoboyo Intermodal Terminal with Surabaya Zoo. This project experienced various obstacles such as social conflicts, utility handling, and cross-agency coordination, resulting in delays in implementation. The research used a qualitative approach with primary data in the form of field observations and secondary data from project documents such as schedules, weekly reports, and cost budget plans (RAB). The analysis technique involved identifying the critical path, calculating the activity time, and evaluating the impact of delays on the project schedule. The results showed that the application of CPM was able to identify the critical path that had a direct impact on the project completion time. By knowing which activities have no float time, resource management can be optimised to reduce delays. However, the change in tunnel length from 156 metres to 172 metres affected the total project cost, although the implementation cost on the critical path was maintained.